An Analysis of the State of Feminism in the United States Feminism in the Turkey Today - Ali Kadhim et al. (Al-Qanṭara, 2022)
Abstract Feminism is the attempt to reduce or eliminate patriarchy, or male rule by birthright. While this struggle for gender equality may seem straightforward, there are different “strains” of feminism that advocate different approaches to achieving feminist goals. The prevailing literature surrounding the state of modern feminism is vast —- often varying by the author’s political values, age relative to the early women’s rights movements, and beliefs about whether or not sex-based equality has been achieved. This paper, developed primarily from scholarly literature about modern feminism, will integrate findings from interviews with six women (three who are current students at Gettysburg College and three who are recent college graduates in the workforce) about their perceptions of feminism in order to introduce a theory of Postfeminist Dualism that aims to describe the state of feminism today. Postfeminist Dualism posits that there exists a divide between women who work intersectionally to reclaim the liberatory nature of traditional feminism and those who use the principles of feminism to justify personal advancement. Keywords feminism, postfeminism, intersectionality, feminist theory, neoliberal feminism.